2006
DOI: 10.1080/00049530600730419
|View full text |Cite
|
Sign up to set email alerts
|

Environmental concern and behaviour in an Australian sample within an ecocentric – anthropocentric framework

Abstract: Two hundred and ninety-two participants from 126 urban and rural locations across Australia responded to a questionnaire assessing levels of environmental concern and behaviour. The environmental concern items consisted of the Thompson and Barton ecocentric, anthropocentric, and apathy scales, together with the items in the New Ecological Paradigm (NEP) revised scale. The broad picture in terms of sociodemographic variables was that female gender, better education, and being older were associated with higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
117
3
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(158 citation statements)
references
References 20 publications
22
117
3
16
Order By: Relevance
“…The correlation between pro-environmental values and high NEP scores is evident in previous studies (Scott and Willits 1994;Tarrant and Cordell 1997;Ebreo et al 1999;Kaltenborn and Bjerke 2002;Rauwald and Moore 2002;Hunter and Rinner 2004;Berenguer et al 2005;Casey and Scott 2006;Kaltenborn et al 2008;Luo and Deng 2008;Ardahan 2012).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The correlation between pro-environmental values and high NEP scores is evident in previous studies (Scott and Willits 1994;Tarrant and Cordell 1997;Ebreo et al 1999;Kaltenborn and Bjerke 2002;Rauwald and Moore 2002;Hunter and Rinner 2004;Berenguer et al 2005;Casey and Scott 2006;Kaltenborn et al 2008;Luo and Deng 2008;Ardahan 2012).…”
Section: Introductionmentioning
confidence: 65%
“…According to the empirical results of various studies, NEP scale measures pro-environmental beliefs in relation to behavioral intentions, and real pro-environmental behaviors (Scott and Willits 1994;Tarrant and Cordell 1997;Ebreo et al 1999;Rauwald and Moore 2002;Casey and Scott 2006). insist that NEP scale results are associated with beliefs, norms, intentions, and behaviors towards the natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found substantial positive correlations at .20 or more (Bjerke & Kaltenborn, 1999;Kaltenborn & Bjerke, 2002;Schultz & Zelezny, 1999). Some studies have found that women have more positive attitudes towards ecocentrism than men (Casey & Scott, 2006;Karpiak & Baril, 2008).…”
Section: Ecocentric and Anthropocentric Environmental Philosophiesmentioning
confidence: 94%
“…However, after the project increasing the attitude levels, there was no significant difference among the groups' attitude levels. It has been shown that demographic variables such as gender and age did not have an impact on the average attitude levels in most of the researches conducted before (Aytaç&Öngen, 2012;Casey and Scott, 2006;Sam et al, 2010;Shephard et al, 2009;Weber, 2011). This study, as well, proved that demographic variables did not influence participants' attitudes towards the environment before or after the documentary movie activity.…”
Section: Discussion Conclusionand Recommendationsmentioning
confidence: 99%
“…However, age, gender and educational concerns (such as education type and level, scientific knowledge) have been the most studied variables predicting people's environmental concern. Yet, the research results indicate inconsistency in respect to these three socio-demographic variables (Aytaç&Öngen, 2012;Casey and Scott, 2006;Dunlap et al, 2000;Sam et al, 2010;Shephard et al 2009;Weber, 2011). Many other socio-demographic variables were also considered to be influential on attitudes such as academic major, country, ethnic origin, religious beliefs, political tendencies, etc.…”
Section: Introductionmentioning
confidence: 99%